2014
DOI: 10.4172/2157-7633.1000199
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells Therapy in Diabetes Mellitus

Abstract: Human embryonic stem cells (hESCs) have the ability to form cells derived from all three germ layers [23]. hESCs can be induced to differentiate into fetal-like pancreatic cells in vitro using a 33-day, 7-stage protocol [24]. The differentiation protocols for inducing hESCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 91 publications
1
13
0
5
Order By: Relevance
“…Although occurring in low frequency, these results suggest that BMSCs have the ability to differentiate into β-cells. 44 Xi and Bu, 2 found that autologous MSCs transplantation in a rat model of (T2D) resulted in enhanced insulin secretion, increased islet numbers in pancreas and ameliorated insulin sensitivity, suggesting functional effects of MSCs on insulin target tissues which lead to the reduction of blood glucose level as shown in the present work.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Although occurring in low frequency, these results suggest that BMSCs have the ability to differentiate into β-cells. 44 Xi and Bu, 2 found that autologous MSCs transplantation in a rat model of (T2D) resulted in enhanced insulin secretion, increased islet numbers in pancreas and ameliorated insulin sensitivity, suggesting functional effects of MSCs on insulin target tissues which lead to the reduction of blood glucose level as shown in the present work.…”
Section: Discussionsupporting
confidence: 74%
“…According to Kim et al., 23 the majority of diabetes loss pathology can be traced to the decrease and/or dysfunction of beta-cells. 2 Different reasons have been put forward for this decrease, such as oxidative stress, endoplasmic reticulum stress, and amyloid formation toxicity. 24 It must also be noted that, as diabetes cases progress, β-cell mass levels decrease and glucose levels increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sel punca mesensimal tidak berdiferensiasi secara in vivo menjadi jaringan kerangka, melainkan berfungsi sebagai parakrin, yaitu pusat sekretori di lokasi cidera. Sel punca ini mampu memproduksi protein dan sitokin untuk perbaikan jaringan, zat imunomodulator yang dapat menekan inflamasi karena luka maupun karena penolakan transplantasi jaringan oleh tubuh (Azapira et al, 2015;Kay et al, 2017), serta sifat proangiogenik yang berpotensi untuk terapi (Xi dan Bu, 2014).…”
Section: Mesenchymal Stem Cells (Mscs)unclassified
“…Sel punca mesensimal (SPM) merupakan salah satu jenis sel punca yang terdapat pada sumsum tulang, jaringan adiposa, darah tali pusat, dan Wharton jelly dari tali pusat (Azarpira et al, 2015). SPM mampu memproduksi protein dan sitokin untuk perbaikan jaringan, zat imunomodulator yang dapat menekan inflamasi karena luka maupun karena penolakan oleh tubuh (Azarpira et al, 2015;Lozito et al, 2009), serta memiliki sifat pro-angiogenik (Xi & Bu, 2014).…”
unclassified